Education on The Application of The 3J Diet to Increase Knowledge of Diabetes Mellitus Patients in The Community of Bandar Kupa, Percut Sei Tuan District, Deli Serdang District - Irwanto, Reno; Novia, Reni; Maria Ginting, Wira; Br Ginting, Luci Riani (JURNAL PENGMAS KESTRA (JPK), 2023)
Degenerative diseases become dangerous killer diseases if not treated properly. Diabetes mellitus (DM) is a non-communicable disease which can be a complication that causes other dangerous diseases. The incidence of DM is still worrying as a contributor to killer diseases and in North Sumatra the incidence continues to increase every year. Based on the existing number of DM sufferers, 25% of sufferers know that they are DM sufferers, the rest do not know yet and this remaining number has a big risk of causing bodily health problems and a risk of complications from other, more dangerous diseases. Consuming foods high in simple carbohydrates, high in sugar, subjected to a lot of processing and low in complex nutrients and fiber can cause disturbances in the function of the insulin hormone, leading to the emergence of DM. In an effort to treat and increase public knowledge regarding DM disease and control the condition of DM sufferers, this is through the implementation of the 3J diet (right schedule, right amount and right type). This educational service activity was carried out in Bandar Kupa, Percut Sei Tuan District, Deli Serdang district on 5-7 June 2023. This community service activity was carried out through several stages. At the initial stage, observations were carried out, then continued with the planning stage, education, delivery of educational material and the evaluation stage of acceptance of the material that had been delivered during the service education process. The results obtained showed that in terms of participant attendance, there was community enthusiasm in participating in the education provided. The results of the educational evaluation, increasing the knowledge of the community of education participants, decreased with the level of knowledge from less than 48% to 12%, there was an increase in sufficient knowledge before education by 32%, increasing to 68% and the level of good knowledge did not increase, namely at a percentage of 20%.